Device therapy guided by implantable loop recorders: predictors of bradyarrhythmic events. (25th November 2020) - Cardoso, A; Faria, B; Von Hafe, P; Dias, G; Pereira, T; Ribeiro, S; Calvo, L; Rodrigues, B; Alves, A; Fernandes, M; Sanfins, V; Lourenco, A
Abstract: Background: Implantable loop recorders (ILR) improved diagnostic yield in unexplained syncope patients (pts). Data on possible predictive factors for bradycardia requiring device implantation in these pts is limited. We aim to identify clinical predictors for device implantation due to a significant bradyarrhythmia in patients who underwent ILR insertion for the study of syncopal/presyncopal (S/pS) events. Methods: Single-center retrospective study of patients who implanted an ILR for the study of unexplained S/pS episodes between 2013 and 2018. The primary endpoint was a documented bradyarrhythmia requiring device implantation during the follow-up. Results: A total of 251 pts were included. Mean age was 68±15 years and 53% were female. The majority of pts (220; 88%) had normal ejection fraction. Fifty-two (21%) pts had atrial fibrillation (AF). Regarding basal electrocardiographic characteristics, 34 (14%) pts had 1st degree auriculo-ventricular block (AVB), 31 (12%) pts had left bundle branch block (L-BBB), 22 (9%) pts had R-BBB and 13 (5%) pts had bifascicular block. During a median follow-up of 20 (IQR 9–34) months, 74 (29%) pts required device implantation because of a significant bradyarrhythmia (92% pacemaker, 4% CRT, 4% ICD). Median duration from ILR until device implantation was 5 (IQR 1–10) months. The indications were sick-sinus-syndrome in 47 (64%) pts, advanced AV block in 23 (31%) pts and symptomatic slow AF in 4 (5%) pts. Patients who required device implantation were older (73±12 vs 66±15 years, p <0.001), had more hypertension (73% vs 59% p=0.048), a higher prevalence of AF (34% vs 15% p=0.001) and a lower glomerular filtration rate (GFR<60 ml/min: 32% vs 21%, p=0.047). They also had more 1st AVB (22% vs 11%, p=0.026) and intraventricular conduction disturbances (38% vs 25%, p=0.025). There was a trend for a higher device implantation in pts with concomitant 1st AVB and left anterior fascicular block (7% vs 2%, p=0.063) In a logistic regression model, age >75 years (HR: 1.7; 95% CI: 1.1–2.8) and the presence of AF (HR: 1.8; 95% CI: 1.1–3.0) were independent predictors for device implantation. Conclusion: An older age and the presence of AF were independent predictors for device therapy in pts who implanted an ILR for the study of S/pS. These factors may identify a higher risk group and should be considered in the initial workup of these pts. Funding Acknowledgement: Type of funding source: None